Profile of tuberculosis patients in Natal-RN, Brazil, from 2010 to 2018: a documentary study - Andrade Júnior, Francisco Patricio de; Alves, Thiago Willame Barbosa; Mendes, Italy Heibe Aciole; Farias, Brenda Kercya da Silva; Cordeiro, Laísa Vilar; Lima, Edeltrudes de Oliveira (Scientia Plena, 2019)
The present study aimed to elucidate the epidemiological profile of tuberculosis patients in Natal-RN between the years 2010 and 2018. This was an epidemiological, retrospective and documentary study, in which the recovery of the secondary data occurred from the “Departamento de Informática do Sistema Único de Saúde (DATASUS)” in Brazil. The following variables were studied: year of notification, gender, age, schooling, area of residence, ethnicity and factors that facilitate the onset of tuberculosis. Statistical association was performed using the Chi-Square test. In the year 2011, the highest percentage of notifications for tuberculosis was received (12.4%) in Natal-RN. The profile of the affected individuals was predominantly male (69.5%), between 20 and 39 years of age (43.8%), low educational levels (41.3%), mulattoes (68.2%) and urban residents (94.1%). When gender was associated with factors that facilitate the onset of tuberculosis, it was observed that males presented higher percentages of positivity for Human Immunodeficiency Virus (HIV) (16.3%), Acquired immunodeficiency syndrome (AIDS) (15.8%), alcoholism (34%) and smoking (13.5%), while in females the highest rates of this correlation were with Diabetes mellitus (10.4%). In addition, a statistically significant association was found between gender with tobacco and alcohol consumption (<0.001) and with the presence of diabetes and Aids (<0.001). The data found in this study may serve as an auxiliary for developing more specific public policies for those most susceptible to tuberculosis in Natal-RN.